Innovative Strategies In Human Resource Management: Optimizing Organizational Performance In The Digital Age - Albi, Khalifachri (Publikasi Indonesia, 2024)
In the ongoing digital era, organizations are faced with various changes that require them to optimize performance in order to remain competitive and sustainable. One approach that can be used to improve organizational performance is through human resource management, given the important role of humans as assets for organizations. The focus of this research is to analyze innovative strategies in human resource management that can improve organizational performance in the digital era. This research uses qualitative methods with data collection techniques through literature studies. After the data is collected, data analysis is carried out which includes the stages of data simplification, data presentation, and conclusion drawing. The conclusion of the research explains that innovative strategies in HRM such as leveraging technology to improve HRM implementation, establishing an innovative and adaptive organizational culture, focusing on developing employees' digital skills, implementing effective talent recruitment and retention strategies, and conducting regular evaluations of these strategies, are able to overcome challenges that may arise during HRM implementation in organizations. Thus, these innovative strategies will help improve HRM implementation, and ultimately optimize organizational performance in the digital era.